Counseling the anti-social client working with resistance and denial - Packard, Norma Glucktern; Microtraining Associates (Amherst, Mass. : Microtraining Associates, 2006)
The purpose of this video is to demonstrate how traditional application of Microcounseling Basic Attending Skills and Basic Influencing Skills may differ when counseling client diagnosed by DSM IV-Axis II Antisocial Personality Disorder (ASPD). Most of antisocial clients avoid participating in counseling by denying or criticizing the value of counseling to solve problems. These clients generally put little value in reflective thinking as a means of changing their behaviors. They generally attend counseling because they have been referred by the courts, by their families or by their employers. The video have been designed to demonstrate the most effective manner in which to use BAS and BIS communication skills
Title from title screen
Counselor : Norma Gluckstern Packard
Keywords: Counseling; Antisocial personality disorders